PENERAPAN STRATEGI PEMBELAJARAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI KRITIS SISWA DI MAS NURUL IMAN - Darmawati; Andi Srimularahmah; Suhardiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Deep Learning learning strategy, examine the improvement of students’ critical literacy skills, and identify the supporting and inhibiting factors in its implementation in expository text learning for Grade XI students at MAS Nurul Iman. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The subjects were 20 students, consisting of 10 male and 10 female students. Data were collected through observation, critical literacy tests, interviews, and documentation, and were analyzed qualitatively and quantitatively. The results showed that the Deep Learning strategy improved students’ critical literacy skills. In the pre-action stage, the students’ average score was 61.75, with a low completion rate. After the intervention in Cycle I, the average score increased to 80, and all students (100%) achieved scores above the Minimum Completion Criteria (KKM). Improvements were observed in understanding the structure of expository texts (91.25%), analyzing content and ideas (82.5%), evaluating arguments (76.25%), relating texts to real-world contexts (75%), and language use and clarity of responses (75%). Students’ learning activities also became more active, interactive, and reflective. Supporting factors included student engagement, group discussions, and teacher guidance, while the main obstacles were differences in students’ abilities and limited discussion time. Therefore, the Deep Learning strategy was effective in improving students’ critical literacy skills in expository text learning.